Muslims’ Participation in Education and Employment as Compared to Other Socio-Religious Categories: An Analytical Study - Parvez, Mohammad; Hasan, Mohd (International Journal of Social Sciences and Management, 2015)
Since, the submission of the Sachar Committee Report (2006), several analytical and descriptive studies have been undertaken to analysis the socio-economic and educational conditions of Muslims in India. Many researchers, educationists, thinkers, politicians, policy makers and common Muslims believe that education is the only panacea to eradicate the each and every ails of Muslims, and it is the only mechanism by which not only their status can be raised but also facilitate their entry into better paid job. This paper aims to evaluate the available evidences on the pattern of Muslim participation in education and employment. It is an attempt to see the Muslims’ participation in education and employment in relation to other Socio Religious Categories of India. Based on different secondary data sets, it attempts to see how the Socio Religious Categories across India have utilised the process of education and achieved educational and employment opportunity higher than the Muslims. Muslims as a homogenous group did not participate actively in the educational development, more especially in the arena of higher education whereas the other Socio Religious Categories have acquired the maximum benefits with the constitutional and political interventions that are taken place in Pre and Post- Independent era. The present paper also try to see the trend of Muslims’ participation in education right from the primary education to higher education as well as sector wise employment and work activities as compared to other Socio Religious Categories. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12196 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 114-118